Cost efficiency and welfare performance of banks: Evidence from an emerging economy - David Adeabah; Charles Andoh (International Journal of Managerial Finance, 2019)
The study examines the relationship between the consequential social cost of market power (i.e., welfare performance of banks) and cost efficiency using data covering the period 2009 to 2017 from the Ghanaian banking industry. The study adopts the Ordinary Least Squares (OLS), Fixed Effect (FE) panel regression and the Quantile regression (QR) approaches to control for heterogeneity and provide increased room for policy relevance. The Two-Stage Least Squares Instrumental Variables (2SLS-IV) regression is used to ensure the robustness of the findings against the problem of possible reverse causality. The results indicate a positive relationship between banks' welfare performance and cost efficiency, which suggests that greater cost efficiency hedges welfare losses. In other words, welfare gains and cost-efficient banks are not mutually exclusive. Also, the results show evidence that the sensitivity of welfare gain to cost efficiency depends on the knowledge of local market dynamics. Further, the findings from the QR estimation suggest that, but for welfare loss at low (Q.25) to the median (Q.50) quantiles, cost efficiency is a necessary and sufficient condition to hedge the welfare losses. The results demonstrate that financial consumer protection cannot be achieved without cost efficiency in the presence of both foreign banks and high market knowledge. Therefore, our paper suggests an integrated cost efficiency policy approach that has the complementary effect of a robust information sharing mechanism and incentives to hedge against welfare losses in the banking sector of emerging economies. Moreover, if welfare gain is synonymous with cost-efficient banks, then the presence of a quiet life is typical of financial consumer protection. This study provides insight into the importance of cost efficiency to the public policy of financial consumer protection in an era of foreign banks' dominance. From the review of prior literature, this paper is the first to apply the QR estimation technique to examine the effect of cost efficiency throughout the conditional distribution of bank welfare performance rather than just the conditional mean effect of cost efficiency.
Keywords: 330; Cost Efficiency; Bank; Welfare Performance; Social Cost; Financial Consumer Protection; Quantile Regression